PENDIDIKAN KARAKTER PERSPEKTIF K.H HASYIM ASY’ARI - Kustiana Arisanti; M. Bahrul Lahut (Mozaic : Islam Nusantara, 2021)
One of the causes of the moral crisis of society and youth is the development of times and technology where everything can be accessed easily. Psychologically, the nation’s youth tend to be idealist and express their emotional easily through the real action. Off course, this one requires education that can be a shield so that it can filter them from bad influences that can appear from various directions. Character education is the main answer to improve youth morale, as formulated by K.H Hasyim Asy’ari in his book Adabul Alim Wal Muta’allim Fi Ma Yahtaju Ilaihil Muta’allim. He said that the good character have a higher position, because all actions that are carried out verbally or physically will have no value without realizing it with the good character and noble morals.